The Effect of Static Flexibility and Proprioceptive Neuromuscular Facilitation (PNF) Exercises on the Speed of the Sabit Kick of Pencak Silat Athletes Tapak Suci Putera Muhammadiyah Pekalongan City - Wijaya, M.Riski Adi; Gilang Nuari Panggraita; Bachtiar; Doby Putro Parlindungan (Jurnal Ilmiah STOK Bina Guna Medan, 2025)
This study aims to determine the effect of static flexibility training and Proprioceptive Neuromuscular Facilitation (PNF) on the speed of sabit kicks in pencak silat athletes from Tapak Suci Putera Muhammadiyah, Kota Pekalongan. Kick speed is a critical component in pencak silat performance, as it directly influences the effectiveness of attacks and the ability to score during matches. The research employed a quasi-experimental method using a pretest-posttest control group design. A total of 30 athletes participated, divided randomly into two treatment groups: one receiving static stretching exercises and the other receiving PNF flexibility training, with 15 athletes in each group. Data collection involved measuring the speed of sabit kicks before and after a four-week training program. Data analysis included the Shapiro-Wilk normality test, Levene’s homogeneity test, paired sample t-test, and independent sample t-test, with a significance level of 0.05. The results showed a significant increase in kick speed in both groups after the training interventions (p < 0.05). However, the independent sample t-test revealed no significant difference in the improvement between the static flexibility and PNF groups (p > 0.05). In conclusion, both static flexibility and PNF training methods are effective in improving the speed of sabit kicks in pencak silat athletes. Either method can be utilized as part of flexibility training in athlete development programs. The choice of method may be adjusted based on individual athlete needs, preferences, and training conditions.